2012
DOI: 10.14710/jitaa.37.1.64-69
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF VIRGIN COCONUT OIL ON LYMPHOCYTE AND CD4 IN CHICKEN VACCINATED AGAINST Avian Influenza VIRUS

Abstract: ABSTRAKPenelitian ini bertujuan untuk mencari alternatif pencegahan penyakit avian influenza (AI) pada ayam pedaging melalui peningkatan daya tahan tubuh. Limfosit T akan bereaksi secara langsung melawan antigen yang telah dipresentasikan ke permukaan sel oleh antigen presenting cell (APC). Interaksi Th-CD4 berperan membantu mampertahankan ikatan Th-APC agar tetap menyatu pada saat aktivasi antigen spesifik berlangsung. Asam lemak pada virgin coconut oil (VCO) berpotensi sebagai immunostimulan sehingga mampu m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…For example, lipid abundance can be modified through dietary intake to reduce inflammation and oxidative stress 28 . Virgin coconut oil, which is mainly composed of monolaurin, was able to boost the amount of lymphocyte and CD4 in vaccinated and unvaccinated broiler chickens, acting as an immunomodulator and increasing chicken immunity 29 . Another study suggested that monolaurin plays a significant role in T cell functions and signaling by altering TCR-induced LAT, PLC-Îł, and AKT cluster formation, PI3K-AKT signaling axis, and calcium influx, decreasing cytokine production 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, lipid abundance can be modified through dietary intake to reduce inflammation and oxidative stress 28 . Virgin coconut oil, which is mainly composed of monolaurin, was able to boost the amount of lymphocyte and CD4 in vaccinated and unvaccinated broiler chickens, acting as an immunomodulator and increasing chicken immunity 29 . Another study suggested that monolaurin plays a significant role in T cell functions and signaling by altering TCR-induced LAT, PLC-Îł, and AKT cluster formation, PI3K-AKT signaling axis, and calcium influx, decreasing cytokine production 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Arora et al [69] stated that coconut oil was very effective against various viruses with lipid capsules, such as VV, CV, and also Epstein-Barr virus. Yuniwarti et al [70] investigated the effect of VCO on lymphocyte and CD4 (cluster of differentiating), a surface protein on T lymphocyte, in chicken which had been vaccinated against the avian influenza virus.…”
Section: F Antiviral Action Of Coconut Oilmentioning
confidence: 99%
“…According to DebMandal and Mandal [29], LA and its monoglyceride found in coconut oil are effective in obliterating a wide variety of lipid-coated bacteria by disintegrating their lipid membranes. The MCFAs in coconut oil principally destroy microbial organisms by disturbing their membranes, thus interfering with virus assembly and maturation [69]. Besides, monolaurin is known to produce highly ordered membranes, which is thought to disrupt membrane function by affecting signal transduction due to blockage of promoters, uncoupling of energy systems, altered respiration state, and altered amino acid uptake [72].…”
Section: G Action Mechanism Of Coconut Oil Against Pathogenic Microomentioning
confidence: 99%
“…Virgin coconut oil merupakan obat herbal yang mampu menunjukkan peningkatan aktivitas fagositosis makrofag (Yuniwarti et al, 2013) dan juga mampu meningkatkan jumlah limfosit (Yuniwarti et al, 2012). Virgin Coconut oil mengandung fenol dan triacylglycerol (Marina et al, 2009) sehingga mampu berperan sebagai antioksidan (Nevin dan Rajamohan, 2006).…”
Section: Pendahuluanunclassified